Prevalence of visual impairment and outcomes of cataract surgery in Chaonan, South China - Zhang, Xiujuan; Li, Emmy Y.; Leung, Christopher Kai-Shun; Musch, David C.; Tang, Xin; Zheng, Chongren; He, Mingguang; Chang, David F.; Lam, Dennis Shun-Chiu (PloS one, 2017)
To estimate the prevalence and causes of blindness and visual impairment (VI), and report the outcomes of cataract surgery in Chaonan Region, Guangdong Province, southern China. Cross-sectional population-based survey. A total of 3484 participants including 1397 men (40.1%) and 2087 women (59.9%) aged ≥50 years were examined (94.2% response rate). A two-stage cluster sampling procedure was used to select 3700 participants aged ≥50 years from 74 clusters of Chaonan Region. Participants were examined according to the Rapid Assessment of Avoidable Blindness (RAAB) method. Blindness and visual impairment (VI) were defined by the World Health Organization criteria. Participants with visual acuity (VA) < 6/18 in either eye were examined by ophthalmologists. The primary causes of blindness and VI were reported with reference to the participant's better eye. Prevalence and main causes of blindness, severe visual impairment (SVI), VI and the outcomes of cataract surgery. The standardized prevalence rates of blindness, SVI, and VI were 2.4% (95% confidence interval [CI], 1.9-2.9%), 1.0% (95% CI, 0.7-1.4%), and 6.4% (95% CI, 5.6%- 7.1%), respectively. The principal cause of blindness and SVI was cataract, accounting for 67.1% and 67.6% respectively, and the principal cause of VI was refractive error (46.9%). One hundred and fifty five out of 3484 (4.4%) people (211 eyes) had cataract surgery. Of the 211 eyes that had cataract surgery, 96.7% were pseudophakic. 67.2% of the 211 operated eyes had a presenting visual acuity (PVA) of 6/18 or better. The prevalence of blindness, SVI, and VI was high among rural residents in Chaonan. Cataract remained the leading cause of avoidable blindness. Outcomes of cataract surgery performed in rural private clinics were suboptimal. Quality-control initiatives such as hands-on training program should be introduced to improve cataract surgery outcomes.